Notes on categories of samba and carnival at the carnival chronicle - Alves, Diego Ramiro Araoz (Universidade Estadual Paulista / UNESP, 2011)
The paper proposes a reflection on writings of chroniclers about carnival based on readings of the books “Na roda do samba” and “Samba”, both published in 1933, by Francisco Guimarães and Orestes Barbosa, respectively. The paper seeks to develop the idea that the instability of semantic categories, such as samba and carnival, favors a critical analysis on the historical authority of these writings.